A study on the effects of sea level rise on mangrove ecosystem in Giao Thuy district, Nam Dinh province - Van Doanh Vu; Hong Tinh Pham; Thi Thu Trang Bui (Vietnam Journal of Science, Technology and Engineering, 2020)
Climate change and sea level rise (SLR) have greatly affected the coastal land use of the Nam Dinh province. It has especially impacted the mangrove forests in coastal plain areas. According to the monitoring data from management units, saline intrusion due to SLR tends to expand in scope, affecting and reducing the area of mangrove ecosystems. From this situation, it can be seen that the impact assessment and estimation of economic loss in coastal provinces such as Nam Dinh is incredibly necessary to help the localities proactively respond to climate change and SLR, which is in line with the national target program on climate change. This research, which uses methods of evaluating economic values, aims to quantitatively assess the extent of damage caused by SLR on an area of mangrove forests in Giao Thuy district, Nam Dinh province. The valuation of these impacts will provide a basis for scientists, research institutions, and localities to proactively mitigate and adapt to climate change. Research results show the damage of climate change and SLR to the coastal mangrove forests in Giao Thuy and the risk to agricultural land use in the Nghia Hung and Hai Hau districts. These results also provide warning of the potential damage caused by SLR to dike and irrigation systems in the coastal districts of the Nam Dinh province, which follow Xuan Truong, Giao Thuy, Hai Hau, and Nghia Hung.